PENGARUH TINGKAT INFLASI DAN PENDAPATAN PEGADAIAN TERHADAP PENYALURAN KREDIT RAHN PADA PEGADAIAN SYARIAH DI INDONESIA TAHUN 2007 – 2015 - Yenni Del Rosa, Erdasti Husni Idwar (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
This study aimed to analyze the effect of inflation and income lending rahn pawn againstthe Islamic pawnshop in Indonesia in 2007 - 2015 which will be beneficial for governmentsand companies to make decisions in the future in accordance with the study variables.Data were collected through documentary studies and surveys using secondary data suchas time series data obtained through library research are then processed by descriptiveand inferential statistics. The dependent variable lending rahn while the independentvariable inflation rates and income mortgages. Before the data is analyzed first performedclassical assumption in the form of normality test, multicollinearity, autocorrelation testand test heterokedastisitas. It turns out all the variables meet all the classic assumptionthat the data could dianalisisBerdasarkan summary model of the correlation coefficient0.984 (very strong), the value of R 0.968 square and adjusted R square value of 0.957. Totest the hypothesis used a significance level of 5%. Based on the partial test inflation ratedid not significantly affect lending Rahn while simultaneously the rate of inflation andsignificant effect on the income of mortgage lending Rahn. It can also be seen from theresults of multiple linear regression equation Y = -4.6 million + 151372.269 X1 + 2.305X2 + e.Keywords: inflation ; pawnshops income ; rahn loan portfolio.